Physico-Chemical Properties of Organic Nonlinear Optical Crystal for Frequency Doubling: Morpholinium Hydrogen Tartrate - Renugadevi, R.; Kesavasamy, R. (Asian Journal of Chemistry, 2014)
Nonlinear optical crystal of morpholinium hydrogen tartrate have been synthesized and grown in aqueous solution by slow evaporation technique. The cell parameters of the grown crystal is identified by single crystal X-ray diffraction analysis which confirms that the morpholinium hydrogen tartrate crystallizes in orthorhombic system with noncentro symmetric space group. The powder X-ray diffraction pattern of the grown crystal has been indexed. FT-IR spectrum was recorded to identify the various functional groups of morpholinium hydrogen tartrate. The various kinds of protons and carbons of morpholinium hydrogen tartrate have been identified using 1H and 13C NMR spectral analyses. The range of optical absorption was ascertained by recording UV-visible NIR spectral studies. The TG/DTA studies of the grown crystal has been revealed. The mechanical property of the grown crystal was analyzed using Vickers microhardness studies. The nonlinear optical crystal activity of the crystal is confirmed by Kurtz-Perry powder technique.